CARP SPAWN POTENTIALITY OF PALEZAGHAT (BIHAR) - Prasad, R R (Indian Journal of Fisheries, 2011)
Some observations on the assemibly of fish spawn at Palezaghat during theyears 1974 and 1975 are presented. The spawn wihich is collected in the vascinityof the assembly centre, arrive in the evening and sold to fish farmers. The Quantityof spawn disposed off from this centre constitute only 7% of the total spawnproduced in Bihsr. Private entrepreneurs are taking more interest in spawn tradethan Government agency; The annual turn over of this centre has also beenpresented.